1977
DOI: 10.1007/bf00848439
|View full text |Cite
|
Sign up to set email alerts
|

Aggregative properties of different cell types of the fresh-water spongeEphydatia fluviatilis isolated on ficoll gradients

Abstract: Cell suspensions of the fresh-watersponge Ephydatia fluviatilis have been fractionated by means ofFicoll gradient centrifugation. Three fractions were isolated. The densest contains archeocyte-like cells only; the intermediate fraction is very rich in choanocytes, and the lightest is a mixture of cell types. Earch fraction shows specificaggregative properties and potentialities to reconstitute functional sponges.It appears that the sequence of reconstitution events can be selectively altered by certain disequi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 9 publications
2
30
0
Order By: Relevance
“…A FicollVrografin density gradient protocol was developed by integrating several published protocols (Zhang et al 2003b;De Sutter and Van de Vyver 1977;Uriz et al 1996;Yin and Humphreys 1996) to purify the archaeocytes. Solutions of 3% Ficoll (F) and 38% Vrografin (V) were prepared in sterile CMFSW at a density of 1.0276 g/ml and 1.1486 g/ml, respectively.…”
Section: Archaeocyte Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…A FicollVrografin density gradient protocol was developed by integrating several published protocols (Zhang et al 2003b;De Sutter and Van de Vyver 1977;Uriz et al 1996;Yin and Humphreys 1996) to purify the archaeocytes. Solutions of 3% Ficoll (F) and 38% Vrografin (V) were prepared in sterile CMFSW at a density of 1.0276 g/ml and 1.1486 g/ml, respectively.…”
Section: Archaeocyte Purificationmentioning
confidence: 99%
“…The isolation and purification of specific cell types for the development of cell culture in vitro is therefore difficult. Ficoll or Percoll density gradient centrifugation has been used to fractionate various sponge cell types in order to investigate their aggregative properties (De Sutter and Van de Vyver 1977). These methods have also been employed in the localization of bioactive metabolites in sponge cells (Uriz et al 1996;Flowers et al 1998;Salomon et al 2001).…”
Section: Introductionmentioning
confidence: 98%
“…The cell suspensions obtained can be used to produce small sponge aggregates that may form the starting point for an in vitro culture. Artificial sponge cell dissociation, combined with sponge cell separation techniques using density gradients (De Sutter and Van de Vyver, 1977;De Sutter and Tulp, 1981), is also used to produce primary cell lines for sponge cell culture (see Cell Cultures, below).…”
Section: Short-term Cultivationmentioning
confidence: 99%
“…In Ophlitaspongia seriata, only the cells dissociated from the larvae originate small functional sponges, whereas those from adults are unable to do this (Borojevic & Lévi, 1964). The function and the role performed by different cell types in the ensuing aggregates is better understood by using the technique of cell type isolation, allowing homogeneous cell categories to be used, and by testing the morphogenetic properties of the aggregates in relation with the original cell source (John et al, 1971;De Sutter & Buscema, 1977;De Sutter & Van de Vyver, 1977). In Ephydatia fluviatilis, this technique demonstrated that archaeocytes are able to reconstitute functional sponges without any other cell type (Buscema et al, 1980).…”
Section: Cell Responses During Aggregation In Vitromentioning
confidence: 99%